A COLLECTION OF TICKS (IXODIDAE) FROM SULAWESI UTARA, INDONESIA - L.A. DURDEN (BIOTROPIA, 1989)
Ixodid  ticks  were  collected  from  seven  species  of  endemic  murid  rodents  and  from  vegetation  in Sulawesi Utara,  Indonesia. Adult  ticks belonging  to  the species, Amblyomma babirussae, A. cyprium and Dermacentor  (Indocentor) steini were taken  from  the vegetation.  Immature  ticks assignable  to the genera, Haemaphysalis,  Amblyomma  and  Ixodes  infested  the murids with  Parauromys dominator and Maxomys musschenbroekii being  the  two most heavily  tick-infested host species. The data are  compared  to other  tick records from Sulawesi.